The influence of experiential marketing on repurchasing interest (survey on customers of woven bag products at Biboki art shop Kefamenanu) - Fredirikus Timo; Rikhardus Bria Seran (Sean Institute, 2024)
This study aims to determine the effect of Experiential Marketing on repurchase intention of woven bag customers at the Biboki Art Shop. The population of this study are customers who buy woven bags at the Biboki Art Shop. The sampling technique uses the Accidental Sampling method. The sample in this study amounted to 60 customers with data collection techniques using a questionnaire. The data analysis technique uses multiple linear regression analysis techniques.The results of this study indicate that the elements of Experiential Marketing which include sense, feel think, act, and relate have a positive effect on repurchase intention. This is strengthened and supported by the sig. smaller than the alpha value, namely 0.000 <0.05, meaning that sense, feel, think, act, and relate have a significant effect on repurchase intention, and then it can be seen from the results of the t-count for the variables sense, feel, think, act, and relate greater than t-table (1.98552), meaning that Ho is rejected and Ha is accepted.